Overall aspects of maxillofacial trauma - Denia Morales Navarro; Dadonim Vila Morales (Editorial Ciencias Médicas, 2016)
Introduction: in trauma there is a host (patient) and a vector of transmission (motor vehicle, gun, etc.). Objective: to conduct a literature review on general aspects of maxillofacial trauma, including general concepts, characteristics of the region and maxillofacial trauma, epidemiology and statistical registration of trauma. Methods: a literature review was conducted in the period from November-December 2014 on Web of Sciences' impact journals (40 journals) and 1 Cuban. Three books were evaluated. Databases of MEDLINE, PubMed and SciELO with the use of descriptors: "trauma", "maxillofacial trauma", "epidemiology" were consulted. Articles in English and Spanish language, preferably publications in the last five years were included. 132 articles were obtained. The study was limited to 55. Data analysis and integration: concepts such as that of trauma, as well as addressing the characteristics of the region and its traumatology, are a starting point to this topic. We observed a tendency towards changing epidemiologic patterns. The implementation of a trauma statistic record is key to a system for the management of these patients. Conclusions: review of the literature allows reviewing concepts such as trauma, defined as an individual's experience of an event or condition that is enduring a real or perceived threat to their lives and safety, or that of a caretaker or familiar. The main causes of these fractures are world traffic accidents, assaults, falls and sports-related injuries. Maxillofacial injuries range from simple to complex and can involve skin, soft tissues and bones. Facial fractures often involve serious morbidity and occasionally fatal. The implementation of a statistical register of trauma involves controlling and improving the quality of trauma care programs.